Impact of Adoption of International Financial Reporting Standards and Financial Crisis on Accounting Quality of Australian Listed Companies - Alappatt, Thomas Mathew (Curtin University, 2020)
The study investigated whether the adoption of International Financial Reporting Standards (IFRS) and the financial crisis effected the accounting quality of Australian listed companies. Earning management, timely loss recognition and value relevance are used to evaluate accounting quality. It is found that both the events have not affected the accounting quality because of the quality of Australian Accounting Standards Board standards used before adoption of IFRS and a good regulatory system in Australia.